2021
DOI: 10.1007/s11252-021-01173-9
|View full text |Cite|
|
Sign up to set email alerts
|

Estimating carbon storage in urban forests of New York City

Abstract: Forests play an important role in mitigating many of the negative effects of climate change. One of the ways trees mitigate impacts of climate change is by absorbing carbon dioxide and storing carbon in their wood, leaves, roots, and soil. Field assessments are used to quantify the carbon storage across different forested landscapes. The number of trees, their size, and total area inform estimates of how much carbon they store. Urban forested natural areas often have greater tree density compared to trees plan… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…Therefore, it was determined that forests with a high understory coverage rate would be considered to have a higher level of erosion control. The level of carbon storage varies according to forest stand type, species, and age [69,70]; therefore, the level of carbon storage was assumed to be consistent across characteristics such as forest type, species, age class, and stand density. Based on previous studies [71,72] that suggest a higher canopy density contributes to greater carbon storage, categorization was performed according to canopy density ratios [58].…”
Section: Survey Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it was determined that forests with a high understory coverage rate would be considered to have a higher level of erosion control. The level of carbon storage varies according to forest stand type, species, and age [69,70]; therefore, the level of carbon storage was assumed to be consistent across characteristics such as forest type, species, age class, and stand density. Based on previous studies [71,72] that suggest a higher canopy density contributes to greater carbon storage, categorization was performed according to canopy density ratios [58].…”
Section: Survey Designmentioning
confidence: 99%
“…Low: low canopy density (less than 40% canopy cover area by trees) Medium: medium canopy density (canopy cover area of 41~70%)High: high canopy density (more than 71% canopy cover area by trees)[58,69,70] KRW 10,000 = USD 7.69 (23 November 2023).…”
mentioning
confidence: 99%
“…For example, urban forests help reduce the urban heat island effect (Alonzo et al, 2021), they support management of stormwater runoff (Selbig et al, 2022), and they are both comprised of and are habitat for various animal and plant species (Derby Lewis et al, 2019). Further, benefits of urban forests including air quality improvement (Lai and Kontokosta, 2019), carbon sequestration (Nowak et al, 2013;Pregitzer et al, 2022), community cohesion (Campbell et al, 2016;Svendsen et al, 2016), and mental well-being (Berman et al, 2021), among others, are increasingly demonstrated and understood. Despite the increasing recognition of the roles that urban forests play, recent work indicates they are declining throughout the United States (Nowak and Greenfield, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The urban forest plays an important role in maintaining and improving the urban environment and is attracting more and more attention [ 14 , 16 ]. The urban forest not only plays an extremely important role in improving the urban microclimate, maintaining the balance between carbon dioxide and oxygen [ 17 ], alleviating the urban “heat island effect” [ 18 ], and purifying the air [ 19 , 20 ]. In addition, it can enrich urban characteristics and the urban landscape and provide recreation and social communication space for residents [ 21 ].…”
Section: Introductionmentioning
confidence: 99%